2000
DOI: 10.1046/j.1365-8711.2000.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks and the separation of cosmic microwave background and astrophysical signals in sky maps

Abstract: We implement an independent component analysis (ICA) algorithm to separate signals of different origin in sky maps at several frequencies. Owing to its self‐organizing capability, it works without prior assumptions on either the frequency dependence or the angular power spectrum of the various signals; rather, it learns directly from the input data how to identify the statistically independent components, on the assumption that all but, at most, one of the components have non‐Gaussian distributions. We have ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 28 publications
0
83
0
1
Order By: Relevance
“…The region analysed is almost identical to the one in Baccigalupi et al (2000): it is a squared patch (340 × 340 pixels) with side of about 20…”
Section: A Cmb Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…The region analysed is almost identical to the one in Baccigalupi et al (2000): it is a squared patch (340 × 340 pixels) with side of about 20…”
Section: A Cmb Applicationmentioning
confidence: 99%
“…For example, available prior information about the signals can be used in a regularised inversion via Wiener filtering and maximum entropy methods, either on small sky patches (Hobson et al 1998) or on the whole sky (Bouchet & Gispert 1999;Stolyarov et al 2002). It has been shown that under certain independence assumption on the signals, the map-operating algorithms based on Independent Component Analysis (ICA) techniques can be applied on sky patches (Baccigalupi et al 2000) as well as on the whole sky (Maino et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICA is more computationally intensive than PCA, and obviously has a lower compression efficiency in terms of residual rms error, but it provides a better separation of mixed components (e.g. Baccigalupi et al 2000 [3] or Bijaoui, this conference). Contrarily to Principal Components, Individual Components are sensitive to localized, oriented, and bandpass-selective features when trained with "natural" image data (Bell & Sejnowski [6]), a property shared with the spatial receptive fields of simple cells in mammalian cortex.…”
Section: Dimensional Reduction and Feature Extraction Of Pixel Datamentioning
confidence: 99%